2018
DOI: 10.3389/fonc.2018.00567
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Atypical Teratoid Rhabdoid Tumor in Adults

Abstract: Background: Atypical teratoid/rhabdoid tumor in adults is a relatively rare malignant neoplasm. It is characterized by the presence of rhabdoid cells in combination with loss of either the INI1 or BRG1protein from the tumor cells.Methods: A systematic review was conducted using MEDLINE using the terms “atypical teratoid rhabdoid tumor” AND “adult.” The systematic review was supplemented with relevant articles from the references. Cases were included if the pathology was confirmed by loss of INI1 or BRG1. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 59 publications
6
70
1
Order By: Relevance
“…ATRT is a highly malignant neoplasm associated with a poor prognosis. It is primarily found in infancy; however, it has been diagnosed both antenatally and in adults [1,10,17]. Due to the lack of large prospective studies regarding ATRT, there is still uncertainty regarding the optimal treatment for these children and therefore, management strategies vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATRT is a highly malignant neoplasm associated with a poor prognosis. It is primarily found in infancy; however, it has been diagnosed both antenatally and in adults [1,10,17]. Due to the lack of large prospective studies regarding ATRT, there is still uncertainty regarding the optimal treatment for these children and therefore, management strategies vary.…”
Section: Discussionmentioning
confidence: 99%
“…Germline mutations of SMARCB1/SMARCA4 have also been associated with poorer survival [10,13,27,28], while newer evidence purports an association with molecular subgrouping [17,31]. Germline mutations of SMARCB1 appear to predispose patients to synchronous rhabdoid tumors within and out-with the CNS [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of AT/RT is poor both in adults and in the pediatric population. Chan et al reported the average survival rate of adult AT/RT was 20 months [8]. This is comparable to the reported median survival of 13.5 to 16.8 months in the pediatric population [10,25].…”
Section: Discussionmentioning
confidence: 61%
“…Ostrom et al reported that the most common location in adults is the cerebral hemisphere, followed by the sellar region [7]. In contrast, Chan et al found that the most common location was the sellar region (46%), followed by cerebral hemisphere (32%) [8]. Sellar AT/RTs were reported to be almost exclusively in females and not in the pediatric population [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Atypical teratoid/rhabdoid tumour (AT/RT) is a malignant neoplasm representing less than 5% of central nervous system tumours [7,11]. Although this tumour is typically seen in the pediatric population, cases of AT/RT have been reported in adults [2]. The most common locations in adults are the cerebral hemisphere and the sellar region [2,18].…”
Section: Introductionmentioning
confidence: 99%